Waqf Model for Climate Change: A Delphi Method Approach - Sukmana, Raditya; Rusydiana, Aam Slamet (SMART Insight, 2023)
Waqf as one of the instruments of Islamic philanthropy has an important role in supporting the achievement of SDG-13. This is shown by the purpose of waqf in preserving the environment, which in turn affects climate change. This research aims to prioritize waqf aspects in achieving SDGs goal 13, namely Climate Action. The analysis method used in this research is the Delphi method with a questionnaire. In addition, the data also used in this study are the results of interviews with academics, practitioners and regulators of waqf and Islamic economics in general. Based on the results of the analysis, it was found that of the 14 variables of waqf aspects for SDG-13, 13 variables were agreed upon by experts and 1 variable was not agreed upon, namely related to the waqf model, namely waqf-zakat. Then regarding the attention criteria, the most important variable in waqf development according to SDG-13 is the environment. In Maqashid Syariah, the most important variable in waqf development according to SDG-13 is bi'ah. And in the Waqf model, the most important variable in waqf development according to SDG-13 is waqf-sukuk.